Operando Studies of the Electrochemical Dissolution of Silver Nanoparticles in Nitrate Solutions Observed With Hyperspectral Dark-Field Microscopy - Wonner, Kevin; Rurainsky, Christian; Tschulik, Kristina (Frontiers in Chemistry, 2020)
Since nanoparticles are frequently used in commercial applications, there is a huge demand to obtain deeper insights into processes at the nanoscale. Especially, catalysis, chemical and electrochemical reaction dynamics are still poorly understood. Thus, simultaneous and coupled opto-and spectro-electrochemical dark-field microscopy is used to study in situ and operando the electrochemically driven dissolution mechanism of single silver nanoparticles in the presence of nitrate ions as non-complexing counter-ions, herein. Hyperspectral imaging is used to probe the intrinsic localized surface plasmon resonance of individual silver nanospheres before, during and after their electrochemical oxidation on a transparent indium tin oxide (ITO) electrode. Furthermore, optical video imaging was performed for additional information. Based on the complete loss of spectral information and intensity, a dissolution of the particles during the reaction was concluded. This way it is revealed that the dissolution of individual particles proceeds over several seconds, indicating a hindrance by the nitrate ions. Only electrochemical analysis does not provide this insight as the measured current does not allow distinguishing between successive fast dissolution of one particle after another or slow dissolution of several particles in a concerted manner. For comparison, experiments were performed in the presence of chloride ions. It was observed, that the silver chloride formation is an instantaneous process. Thus, it is possible to study and define the reaction dynamics on the single nanoparticle level in various electrochemical systems and electrolyte solutions. Accordingly, operando opto- and spectro-electrochemical studies allow us to conclude, that the oxidation of silver to solvated silver cations is a kinetically slow process, while the oxidation to silver chloride is fast. We propose this approach as a new method to study electrocatalyst materials, their transformation and degradation under operando conditions.